Qualidade acústica e intelegibilidade da fala em salas de aulas da Universidade Federal de São Carlos - Jabur, João Pedro Vilela (Universidade Federal de São Carlos, 2025)
Speech intelligibility is a factor of great impact on learning in educational environments. For communication to be effective in lecture-based classes, these spaces must be acoustically adequate, allowing for the full development of the teaching and learning process. In this work, three classrooms with distinct acoustic solutions were characterized in the Theoretical Class Buildings (ATs) at the Federal University of São Carlos (UFSCar): sprayed cellulose (AT5), fiber ceiling tiles (AT10), and no treatment (AT9). The methodology was based on measuring each room’s impulse response, and, through computational post-processing, the main objective parameters specified by ISO 3382 for assessing acoustic quality and speech intelligibility were calculated, such as Reverberation Time (T60), Clarity (C50), Definition (D50), and the Speech Transmission Index (STI). The results revealed a clear disparity: the untreated room (AT9) was considered highly reverberant, with an average T60 exceeding 1.6 s, while the treated rooms exhibited significantly shorter reverberation times. Consequently, AT9 was characterized as a room with low clarity and definition, with consistently negative C50 values (below –4 dB). Among the acoustic solutions, the fiber ceiling (AT10) proved to be the most balanced and efficient, providing good reverberation control at low and mid frequencies. The sprayed cellulose solution in AT5 showed satisfactory performance at mid and high frequencies, though inferior performance in low-frequency bands. Regarding STI, the treated rooms presented results between 0.730 and 0.740, classified as “Good”, whereas AT9 (STI 0.600) was positioned at the lower limit of the same category. It is concluded that some classrooms on the São Carlos campus do not provide adequate conditions for speech intelligibility. Therefore, the acoustic quality of classrooms should be a criterion in efforts to improve institutional infrastructure.
Acoustic quality and speech intelligibility in classrooms at the Federal University of São Carlos
Keywords: Acústica de salas; Intelegibilidade da fala; Parâmetros objetivos; CIENCIAS EXATAS E DA TERRA::FISICA::AREAS CLASSICAS DE FENOMENOLOGIA E SUAS APLICACOES::ACUSTICA; 3. Saúde e Bem-Estar; 4. Educação de Qualidade